2021
DOI: 10.3389/fmed.2021.609773
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Classification Tree Models in Rheumatoid Arthritis Using Combination of Matrix-Assisted Laser Desorption/Ionization Time-of-Flight Mass Spectrometry and Magnetic Beads

Abstract: Background: There is no simple method for early diagnosis and evaluation of rheumatoid arthritis (RA). This study aimed to determine potential biomarkers and establish diagnostic patterns for RA using proteomic fingerprint technology combined with magnetic beads.Methods: The serum protein profiles of 97 RA patients and 76 healthy controls (HCs) were analyzed by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF-MS) with weak cationic exchange (WCX) magnetic beads. Samples w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…However, studies on 14-3-3ϵ in pulmonary fibrosis, especially in CTD-ILD, are scarce. Similarly, the level of transthyretin in the BALF of patients with SSc-ILD was elevated, as detected by proteomic methods (15,18,20). One study found that transthyretin stimulates the production of collagen I and immunoglobulin-binding proteins in fibroblasts, which participate in endoplasmic reticulum stress activation and profibrosis through mitochondrial oxidative stress in cardiac amyloidosis (44).…”
Section: Proteomics Studies In Ssc-ildmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies on 14-3-3ϵ in pulmonary fibrosis, especially in CTD-ILD, are scarce. Similarly, the level of transthyretin in the BALF of patients with SSc-ILD was elevated, as detected by proteomic methods (15,18,20). One study found that transthyretin stimulates the production of collagen I and immunoglobulin-binding proteins in fibroblasts, which participate in endoplasmic reticulum stress activation and profibrosis through mitochondrial oxidative stress in cardiac amyloidosis (44).…”
Section: Proteomics Studies In Ssc-ildmentioning
confidence: 99%
“…In addition, Landi’s team found that 14-3-3ϵ was increased in the BALF proteome of SSc-ILD patients compared with nonsmokers ( 18 , 20 ). In inflammatory and autoimmune diseases, 14-3-3-ϵ, as a component of the TNFR2 complex, restricts the activation of NF-κB through PI3K/Akt/mTOR signaling and stimulates the activation of C/EBP-β, thus guiding the plasticity of macrophages ( 43 ).…”
Section: Proteomics Studies In Different Ctd-ild Subtypesmentioning
confidence: 99%
“…MALDI-TOF MS technology combined with magnetic beads has been widely used in the study of a variety of diseases and has led to the discovery of a variety of protein biomarkers, including for cancer ( 12 ), immune diseases ( 13 ), and endocrine diseases ( 14 ). MALDI-TOF MS technology combined with magnetic beads can directly detect all kinds of complex biological samples (e.g., urine, blood, cerebrospinal fluid, tissue biopsies, and even tear samples).…”
Section: Introductionmentioning
confidence: 99%